Measures of decision-making ability and functional outcomes in older adults: results from a scoping review in the ARMCADA study - Karpouzian-Rogers, Tatiana; Dworak, Elizabeth M.; Bucko, Patricia; Ho, Emily H.; Ece, Berivan; Mather, Molly A.; Novack, Miriam A.; Pila, Sarah; Hosseinian, Zahra; Hall, LaToya; Mkhize, Tarry; Bassard, Adrianna M.; et al. (Frontiers in Psychology, 2025)
BackgroundThough often not routinely assessed in older adults, declines in decision-making (DM) abilities are often observed in aging and may lead to adverse outcomes in multiple aspects of daily functioning. The Advancing Reliable Measurement in Cognitive Aging and Decision-making Ability (ARMCADA) research initiative seeks to address these issues. This scoping review investigates the current published literature on existing DM measures in aging samples, with emphasis on the domain of functional outcomes, defined as skills or behaviors related to one's ability to live independently.MethodsWe identified studies published between 2018–2023 using key words related to DM abilities and functional outcomes in aging populations through multiple databases. Titles and abstracts were first reviewed by two reviewers, full texts were then screened, and data were extracted from included articles.ResultsThe scoping review identified 16,278 articles across domains with adults aged 45 and older. After screening and extraction, 705 total articles were included; 301 were related to functional outcomes and, from these, 231 distinct measures were identified. Mode of administration of most measures were self-administered with supervision, followed by examiner-administered, and most were conducted with clinical samples (e.g., MCI/AD, chronic health conditions, and Parkinson's disease, or clinical samples and a control group).DiscussionThe goal of the current scoping review is to provide a comprehensive examination of the current DM measures in older adults; this article focuses on the domain of functional outcomes. This scoping review guides a project to create and validate measures that can efficiently assess DM abilities in older adults across the cognitive aging spectrum.